2020
DOI: 10.21511/bbs.15(3).2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the stability of the banking system based on fuzzy logic methods

Abstract: The functioning of the country’s banking system is the basis for ensuring its economic development and stability. The state of the banking system often causes financial crises; therefore, ensuring its stable work is one of the main tasks of monetary policy. Meanwhile, it is important to find approaches to a comprehensive assessment and forecasting of the stability of the banking system that would allow obtaining adequate results.Based on a sample of data generated for the period from 2008 to the 1st quarter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Despite the use of different methods and a different set of indicators for assessing stability, Blahun et al (2020) obtained results similar to our study, namely, stability is determined at a medium level, which on the Harrington desirability scale can be considered a satisfactory condition. In addition, the authors also note that it is influenced by both internal and external factors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Despite the use of different methods and a different set of indicators for assessing stability, Blahun et al (2020) obtained results similar to our study, namely, stability is determined at a medium level, which on the Harrington desirability scale can be considered a satisfactory condition. In addition, the authors also note that it is influenced by both internal and external factors.…”
Section: Discussionsupporting
confidence: 79%
“…Almahadin et al (2020), studying the relationship between financial stability and stability of the banking system using the FMOLS approach on the example of Jordan, state that most indicators of banking reliability have a positive effect on financial stability when a stable interest rate policy plays a key role in this. Blahun I. S. et al (2020) modeled the stability of the banking system of Ukraine, which is the main element of its financial system using the method of fuzzy Mamdani logic, assessed the level of stability as average and proved that the state of the banking stability system is largely determined not only by internal but also external factors at both national and international levels.…”
Section: The Methodological Approach For Analyzing Financial Stabilitymentioning
confidence: 99%
“…-as input. To estimate the cost of particular banking service in [1] it is proposed to use a functional dependence of the Cobb-Douglas type:…”
Section: Resultsmentioning
confidence: 99%
“…The issue of studying the activities of banks in conditions of uncertainty is extremely complex. Often, the efficiency of the bank's operation is first singled out -this is the ratio of effects to invested resources; it can also be defined as a measure of the rationality of action [1]. The authors in [2] interpret efficiency as maximizing production, which arises as a result of proper allocation of resources with given constraints on supply (ie costs incurred by producers) and demand (ie consumer preferences).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Meanwhile, a public apology can be recognized as one of the possible means of smoothing over the moral harm caused to the owner of personal data that was used in the process of credit fraud, provided that they are accepted by the victim. On the contrary, it is unlikely that an apology can be taken into account in situations of damage caused by fraud to the business reputation of a credit institution and its organizational integrity due to a decrease in the credibility of the organization, loss of trust of stakeholders and a fall in the market value of shares, as well as undermining public morality [12] (on the intermediary function of credit institutions in world practice, the dependence of national economies' indicators on changes in the banking sector and on other circumstances that determine the extraordinary nature of these negative consequences, see [13][14][15][16]. Based on the foregoing, it should be concluded that in all cases when deciding whether there is a fact of the atonement of harm and, therefore, the possibility of applying clause "k" part 1 of Art.…”
Section: Discussionmentioning
confidence: 99%